Assessment of pollution and risk of soil pollution in Bor using different indices - Nikolić Violeta; Staletović Novica; Presburger-Ulniković Vladanka; Jovanović Ivan (Bakar)
The paper analyzed the content of pollutants and harmful elements in the soil in Bor during the year 2022. The concentrations of Cu, Ni, Cr, Pb and As in the soil were determined at 15 locations near the Bor Mining and Smelting Complex. Soil pollution at individual locations was assessed based on the measured concentration of elements and certain factors and pollution indices (contamination factor (Cf), degree of contamination (Cd), modified degree of contamination (mCd), geo-accumulation index (Igeo), pollution load index (PLI), Nemerow Pollution Index (PIN), individual and total index of potential risk of environmental pollution). Pearson's correlation coefficients indicated a strong correlation between Cu and Pb (0.887), Cu and As (0.953), Pb and As (0.960) and Cr and Ni (0.889). The results showed that there is an uneven distribution of pollutants and harmful elements in the investigated area. Elevated content of the mentioned elements was determined mostly for Cu, which is expected, and only at one location for Pb and As. Based on the obtained indices and factors, the overall quality of the soil in the selected locations is variable. It was found that the sites varied from uncontaminated to heavily polluted at the Park location - the old center of Bor, which had the highest risk of pollution.